(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objectives of this research are to (1) study success and sustainability factors that are important components of organic farming, (2) study organic farming models that are successful and can be extended to other areas, and (3) propose the policy and operational recommendations in driving organic agriculture in Nakhon Nayok Province. This research employed the mixed method, gathering data by questionnaires distributed to 400 samples who were the farmers both interested and uninterested in the participatory organic certification project. The in-depth interviews and focus groups were conducted with the group of 60 successful and unsuccessful farmers in organic farming for gaining qualitative data. Quantitative data was analyzed, using descriptive statistics; numbers, percentages, means, and standard deviations, whereas the qualitative data were analyzed using content analysis, summary, and interpretation. The research found that: 1) There were many important component factors contributing to the success and sustainability in organic farming which were health, environmental, social and economic factors. 2) The model of successful organic farming which could be expanded to other areas were (1) the farmers being stimulated to join the project by knowledge, understanding, and being health-concerned, (3) analysis of environmental conditions that affect organic farming and participation in the Participatory Organic Certification Project (PGS), which were natural resources, community, economic, social and politic environments, (4) supporting factors of production Continuous training and knowledge on various matters (5) strengthening of farmer groups (6) classification or selection of farmer groups who applied to join the project (7) training to develop knowledge in organic farming, and (9) evaluation at various stages. 3) Policy and operational recommendations for driving organic agriculture in Nakhon Nayok Province are (1) planning, (2) monitoring and evaluation, (3) integration with other relevant government and private agencies, (4) building confidence among consumers, (5) marketing (6) adding added value to products, (7) project integration, (8) determining positions for those responsible for the project, (9) determining responsible departments, (10) setting as the national agenda, (11) creating incentives, and (12) establishing a fund.